Potential of zero charge as a sensitive probe for the titration of ionizable self-assembled monolayers - Ramírez, Pablo (2008)
Potential of zero charge and interfacial capacitance values of x-mercaptoalkanoic acid monolayers deposited on Au(111) are derived from immersion current transients, and are applied to the analysis of their acid properties. Potential of zero charge and capacitance titration curves extend over six pH units, and exhibit apparent pK1/2 values that vary with electrolyte concentration. Electrostatic adsorption of protons at the monolayer-solution boundary provides a quantitative explanation of these observations, and leads to a diffuse layer corrected pKa value of 4.3, which is independent of the thiol chain-length.